Financial Ratio Analysis to Assess The Performance of Mining Sector Company in United Tractor Semen Gresik Ltd., Period 2011-2015 - Keisya Oviriska Putri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to assess the performance of the company using financial ratios and to analyse the comparative performance of the company by connecting these ratios towards the average value of the company. The type of this research is descriptive-quantitative research is a study conducted with the main objective to provide a picture or a description of a situation objectively. The method used to measure the financial performance of the company is the financial ratio analysis of liquidity ratios (current ratio, quick ratio and cash ratio); solvency ratio (debt to asset ratio, debt to equity ratio, long-term debt to equity ratio, long-term debt to asset ratio, and the time interest earned); the ratio of profitability (profit margin, return on assets, and return on equity); activity ratio (average collection period, fixed asset turnover, and total asset turnover). Based on the results of research conducted at United Tractors Semen Gresik Ltd., it shows that the company's financial performance is average. This result suggests that in improving the company’s financial performance, they should raise the capital, reduce the fixed assets, reduce debts, improve the bargaining power and efficiency and also reduce the cost of company's activities.Keywords: Mining Industry, Liquidity Ratios, Solvency Ratios, Profitability Ratios, Activity Ratios.